2010
DOI: 10.1007/s11431-010-3153-y
|View full text |Cite
|
Sign up to set email alerts
|

Statistical research on the motion properties of the magnetotail current sheet: Cluster observations

Abstract: The origin of the flapping motion of the earth's magnetotail current sheet is one of the most important problems in the magnetotail dynamics. Using Cluster data, we make a statistical research on the motion properties of the magnetotail current sheet of 2001 and 2003. We calculate the velocities of the magnetotail current sheet using new methods and obtain the distribution of the magnetotail current sheet velocities in the X-Y plane in GSE coordinate system. Our results show that although most of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…The plasma sheet encompasses the magnetotail current sheet and the flapping of the current sheet is frequently observed (Sergeev et al, 2004;Sun et al, 2010). This flapping often results in a spacecraft repeatedly crossing the tail current sheet, during which a reduction in magnetic field magnitude could be observed.…”
Section: Observation Overviewmentioning
confidence: 99%
“…The plasma sheet encompasses the magnetotail current sheet and the flapping of the current sheet is frequently observed (Sergeev et al, 2004;Sun et al, 2010). This flapping often results in a spacecraft repeatedly crossing the tail current sheet, during which a reduction in magnetic field magnitude could be observed.…”
Section: Observation Overviewmentioning
confidence: 99%
“…Runov et al also found a longer event (7Re) observed by THEMIS [11]. The flapping movement of current sheet prefer moving up and down in the midnight tail region [9,12].…”
Section: Introductionmentioning
confidence: 86%
“…Their results showed that most magnetotail current sheets propagated from the midnight tail region towards dawn and dusk flanks. Also see in [8,9]. Zhang et al found a same magnetotail current sheet propagated from the midnight tail region toward the dawn flank with TC-1 and Cluster, and his result implied that the flapping movement of current sheet could stretch in a large scale (5Re) along X direction [10].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations